The neuropsychology of cancer and oncology - Noggle, Chad A.; Dean, Raymond S. (Contemporary neuropsychology series., 2013)
Interest in the neurocognitive and sensory impairments resulting from many cancers and their interventions has grown considerably over the past decades as an important aspect of quality of life issues for cancer patients and survivors. The Neuropsychology of Cancer and Oncology features current findings on the neuropsychological effects of these cancers and their treatments along with the most promising neuropsychological and behavioral health interventions available to mitigate these deficits. This edited volume, part of the Contemporary Neuropsychology series, bridges the gap between the kno.